Contagion in major CDS markets for the post Global Financial Crisis: A multivariate AR-FIGARCH-cDCC approach - Konstantinos Tsiaras; Theodore Simos (Argomenti: Rivista di Economia, Cultura e Ricerca Sociale, 2020)
We explore the time-varying conditional correlations of the Sovereing CDS spread returns for Germany, France, China and Japan against USA. We employ a cDCC-AR-FIGARCH model in order to capture potential contagion effects between the markets during the 2011-2018 post global financial crisis. Empirical results do not reject contagion for the country pairs: Germany – France, Germany – Japan and France – Japan while there is little support for contagion among China and the rest of the countries.